Peningkatan Pengetahuan Pengasuhan Orangtua Untuk Mewujudkan Kesejahteraan Anak Usia 5 dan 6 Tahun : Action Research Pada Komunitas Ibu-Ibu Semai Benih Bangsa (SBB) Tapos, Depok - Annisah, Annisah (UI Scholars Hub, 2012)
This research discusses about the lack of knowledge in the SBB Tapos parenting and its association with child welfare. This study explains not only how these problems occurred, but also the potential of what society has to address the problem, and how to overcome them. Overcoming ofproblems conducted with the participation of target communities in a program of action in the form of social action. This research is an applied research that is processed in a qualitative way so that describes each stage of parenting knowledge improvement that has been done. The results of this study show a change in knowledge of target communities regarding which ideal parenting that should be given to children aged 5 and 6 years.